2002
DOI: 10.1128/aac.46.12.3926-3932.2002
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Dependent Accumulation of Norfloxacin and Porin Expression in Clinical Isolates of Klebsiella pneumoniae and Relationship to Extended-Spectrum β-Lactamase Production

Abstract: The relationships between porin deficiency, active efflux of fluoroquinolones, and extended-spectrum ␤-lactamase (ESBL) production were determined for 53 clinical isolates of Klebsiella pneumoniae. Thirty-two ESBL-positive strains (including 22 strains expressing porins and 10 strains lacking porins) and 21 ESBLnegative strains were evaluated. Active efflux of norfloxacin was defined as a >50% increase in the accumulation of norfloxacin in the presence of carbonyl cyanide m-chlorophenylhydrazone (CCCP) in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
48
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 22 publications
6
48
0
2
Order By: Relevance
“…These antimicrobials may select for ESBLEC in previously colonized patients, since ESBL production and resistance to these antimicrobials are linked. The plasmids encoding ESBLs also frequently encode the genetic determinants of trimethoprim-sulfamethoxazole resistance; the association between ESBL production and quinolone resistance is more complex (17,25). The prevalence of ESBLEC colonization in the community is not known.…”
Section: Discussionmentioning
confidence: 99%
“…These antimicrobials may select for ESBLEC in previously colonized patients, since ESBL production and resistance to these antimicrobials are linked. The plasmids encoding ESBLs also frequently encode the genetic determinants of trimethoprim-sulfamethoxazole resistance; the association between ESBL production and quinolone resistance is more complex (17,25). The prevalence of ESBLEC colonization in the community is not known.…”
Section: Discussionmentioning
confidence: 99%
“…several studies have observed that there is a relationship between the balance of porin expression and β-lactam susceptibility in clinical K. pneumoniae isolates [24][25][26][27][28][29][30] . a similar phenomenon has been reported in a patient infected with Salmonella enterica subsp.…”
Section: Alterations In Porin Expressionmentioning
confidence: 99%
“…In an important study of ESBL-producing strains from outbreaks of nosocomial infections (294), ciprofloxacin resistance (caused in part by AcrB overproduction) was strongly correlated with cefoxitin resistance, suggesting that for ␤-lactam resistance, not only the ␤-lactamases and porin depletion but also efflux may make a significant contribution. Similarly, ESBL-producing strains often lack porins and show a stronger efflux of fluoroquinolones (295). The significance of efflux in ␤-lactam resistance was pursued later by the Pagès group (296), who examined cefoxitin-resistant but ceftazidime-susceptible clinical isolates.…”
Section: Klebsiella Pneumoniaementioning
confidence: 99%